VOLTAGE STABILITY ANALYSIS FOR ENSURING POWER SYSTEM STABILITY - Ab Rahman, Luqman Nur Hakim (Universiti Teknologi PETRONAS, 2016)
Distributed generation (DG) is a small scale electrical generation located near to the customer site of the meter. In the distribution system, distributed generation is getting more important because of the increasing electrical energy demands. Placement and sizing of DG has a great impact on the system stability and losses in the distribution network. In this project, a heuristic method has been proposed for placement and sizing of DG for distribution system based on voltage stability index (VSI), showing that the minimum value of the stability index indicates the most sensitive bus in the system that leads to voltage collapse, where the node voltages slowly decline before a sudden drop.